2016
DOI: 10.1155/2016/7484601
|View full text |Cite
|
Sign up to set email alerts
|

The IL-1βReceptor Antagonist SER140 Postpones the Onset of Diabetes in Female Nonobese Diabetic Mice

Abstract: The cytokine interleukin-1β (IL-1β) is known to stimulate proinflammatory immune responses and impair β-cell function and viability, all critical events in the pathogenesis of type 1 diabetes (T1D). Here we evaluate the effect of SER140, a small peptide IL-1β receptor antagonist, on diabetes progression and cellular pancreatic changes in female nonobese diabetic (NOD) mice. Eight weeks of treatment with SER140 reduced the incidence of diabetes by more than 50% compared with vehicle, decreased blood glucose, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Considering the role of proinflammatory cytokines on the pathogenesis of diabetes, population with detectable levels of circulating IL-1β cytokines have increased risk to develop diabetes ( 28 30 ). We speculate that sodium butyrate could relieve diabetes reflected by decreased level of IL-1β.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the role of proinflammatory cytokines on the pathogenesis of diabetes, population with detectable levels of circulating IL-1β cytokines have increased risk to develop diabetes ( 28 30 ). We speculate that sodium butyrate could relieve diabetes reflected by decreased level of IL-1β.…”
Section: Resultsmentioning
confidence: 99%
“…A significant improvement in the first-phase insulin secretion and pancreatic β-cell function was found (325) (Table II). In line with these findings, cucak et al (326) evaluated in female non-obese diabetic (nod) mice, the effects of Ser140, which is a 10-amino-acid peptide antagonist of il-1β receptors (il-1ra), on the progression of diabetes and pancreatic β-cell changes. The study consisted of an 8-week treatment period.…”
Section: Therapeutic Interventions On Inflammatory Mediators For the ...mentioning
confidence: 95%
“…Additionally, SER140 administration changed the immune-endocrine dynamics in the NOD mouse pancreas. The authors suggested that the SER140 treatment can postpone the onset of diabetes in female NOD mice by competing with IL-1β for IL-1β receptors (IL-1R) ( 326 ).…”
Section: Therapeutic Interventions On Inflammatory Mediators For the ...mentioning
confidence: 99%
“…When administered to diabetic KK‐A y mice, the formulation was able to enhance glucose tolerance, insulin sensitivity while decrease free fatty acids in serum, cholesterol, β‐cell death, and IL‐1β production. Likewise, a different peptide antagonist of IL‐1β, SER140, was found to preserve β‐cell mass and delay the diabetes development in NOD mice …”
Section: Cytokines and Therapies That Modulate Their Activitymentioning
confidence: 99%